Heterointerface engineering of lightweight, worm-like SiC/B4C hybrid nanowires as excellent microwave absorbers. Issue 32 (26th July 2019) - Liu, Yuan; Wu, Wen-Wen; Liu, Li-Na; Xing, Zi-Jun; Chen, Xiao-Ming; Liu, Peng
Abstract : A novel, lightweight and excellent microwave absorber of heterointerface engineered SiC/B4 C hybrid nanowires. Abstract : Developing highly efficient electromagnetic wave absorbers with high reflection loss, wide absorption bandwidth, strong thermal stability and light weight is still a challenge at present. Herein, we creatively developed ultralight B4 C-based hybrid nanowires as novel absorbers. The synthesized B4 C nanowires with abundant stacking faults exhibit excellent microwave absorption properties. Heterointerface engineering of the B4 C nanowires was realized by introducing SiC nanoparticles into the nanowires through a multi-step vapor–liquid–solid process. The SiC embedded B4 C hybrid nanowires with a unique worm-like structure achieved a broadband effective absorption up to 4.7 GHz (13.3–18 GHz) at 2.5 mm and a broadband absorption up to 4.9 GHz (7.4–12.3 GHz) at 3.7 mm, which covered the whole X-band. Furthermore, the optimized reflection loss value became −50.81 dB at 11.9 GHz at 3.3 mm thickness, almost three times that of the B4 C nanowires. The significantly improved microwave absorption ability primarily resulted from the enhanced dual dielectric relaxation, that is, electric dipole polarization and interfacial polarization. The low reflection loss values and wide absorption bandwidth of the SiC/B4 C hybrid nanowires, together with their high temperature stability and light weight, make them a good candidate as highly efficient electromagnetic wave absorbers under harsh conditions.